The effect of inflation and interest rates on forward-looking effective tax rates - Christoph Spengel; Jost Henrich Heckemeyer; Frank Streif (Office for Official Publications of the European Communities, 2016)
[Objective] Every year ZEW Mannheim computes measures of corporate effective taxation in Europe based on the Devereux/Griffith methodology. The measures aim at comprehensively reflecting and consistently comparing the effective corporate tax levels in the different member states. For the computation of the effective tax rates, assumptions on economic parameters have to be made - in particular on the values of the inflation and interest rate. Common assumptions on these variables are strictly necessary in order to compare effective levels of taxation across countries in a meaningful way. In some cases these assumptions could interact with the effects of specific tax parameters on the effective tax burdens. For example, capital allowances become less effective in reducing tax burdens in inflationary environments. As a consequence, countries with high capital allowances appear more attractive when inflation is low. This study aims at analysing and quantifying the effect of the real interest and inflation rate on effective tax measures.
Keywords: 330